1997
DOI: 10.1523/jneurosci.17-15-05678.1997
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity of the 22 kDa Thrombin-Cleavage Fragment of Apolipoprotein E and Related Synthetic Peptides Is Receptor-Mediated

Abstract: Potent neurotoxicity is associated with both apolipoprotein E (apoE)-related synthetic peptides and the 22 kDa N-terminal thrombin-cleavage fragment of apoE. Furthermore, the E4 isoform of the 22 kDa fragment is significantly more toxic than the same fragment derived from the E3 isoform, suggesting the possibility of a direct role of apoE-associated neurotoxicity in the pathophysiology of Alzheimer's disease. In the present study, the potential role of cell surface receptors in mediating neurotoxicity was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
88
2
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 68 publications
7
88
2
1
Order By: Relevance
“…The importance of this region of apoE in neurotoxicity is consistent with our previous in vitro observations in which the lipid-binding region of apoE is toxic to cultured neuronal cells (22). The amino-terminal 22-kDa thrombin-cleavage fragment (amino acids 1-191) of apoE4 is also neurotoxic in vitro (51,52), but this toxicity appears to require relatively high concentrations of the fragment and has not yet been confirmed in vivo. The apoE fragments generated in AD brains are different from the 22-kDa thrombin-cleavage products (22), which lack the lipid-binding domain (amino acids 244-272).…”
Section: Discussionsupporting
confidence: 87%
“…The importance of this region of apoE in neurotoxicity is consistent with our previous in vitro observations in which the lipid-binding region of apoE is toxic to cultured neuronal cells (22). The amino-terminal 22-kDa thrombin-cleavage fragment (amino acids 1-191) of apoE4 is also neurotoxic in vitro (51,52), but this toxicity appears to require relatively high concentrations of the fragment and has not yet been confirmed in vivo. The apoE fragments generated in AD brains are different from the 22-kDa thrombin-cleavage products (22), which lack the lipid-binding domain (amino acids 244-272).…”
Section: Discussionsupporting
confidence: 87%
“…ApoE fragments similar to those observed in our study were generated in primary cultured cortical neurons but not in primary cultured astrocytes obtained from transgenic mice expressing apoE4 in both cell types (Lesuisse et al, 2001). Others have shown that the N-terminal 22 kDa thrombin cleavage fragment (amino acids 1-191) of apoE4 is neurotoxic in vitro (Tolar et al, 1997(Tolar et al, , 1999; however, this toxicity appears to require relatively high concentrations of the fragment and has not yet been confirmed in vivo. In addition, the lipid-binding domain of apoE (amino acids 244 -272; Huang and Mahley, 1999;Huang, 1999, 2000) appears to be essential for apoE fragments to have neurotoxic effects in vivo, as demonstrated in our previous study (Harris et al, 2003).…”
Section: Discussionsupporting
confidence: 43%
“…60 This process was suggested to be receptormediated. 58 We did not observe 22-kd ApoE fragments in the ApoE4 transgenic mice with the method that we used, which argues against a role for these fragments in the pathology of the Thy1-ApoE4 transgenic mice.…”
Section: Discussionmentioning
confidence: 65%